The Nationalist-Religious Political Image in the Construction of the News of Ganjar Pranowo's Appointment as a Presidential Candidate - Fullah Jumaynah (Kalijaga Journal of Communication, 2023)
This article attempts to read the political image that was highlighted by Ganjar Pranowo when he was appointed as the presidential candidate of the PDI-P by analyzing news framing from two mass media with quite different ideologies, namely Kompas.com and Republika.co.id. This study uses a descriptive-qualitative approach using the Robert N. Entman framing analysis model. From the research that has been done, it can be interpreted that Kompas.com displays aspects that are embedded directly with symbols that are identical to the PDI-P, such as Soekarno's cap and the venue of for the determination event at the Batu Tulis Palace, which was Soekarno's residence. Apart from that, Kompas.com also displays sources from internal PDI-P. Meanwhile, Republika.co.id displays several emphases linking religious symbols related to Megawati's beliefs and mentioning her attitude as a statesman. In addition, the news displayed by Republika.co.id tends to choose sources from political observers as the title choice, compared to direct opinions from actors or parties who understand.